Public institutions and gender relations in sustainable forest management, Cintalapa, Chiapas - Palacios Vázquez, Ana Lilia; Pérez Nasser, Elia; Pérez Olvera, Ma. Antonia (Revista Mexicana de Ciencias Agrícolas, 2017)
This research analyzes gender relations in two rural communities in Cintalapa municipality, Chiapas, within the La Sepultura Biosphere Reserve and the influence of public institutions related to sustainable forest management. Forest management is based on techno-scientific aspects that prioritize valuable resources in the market at the expense of biodiversity and resources relevant to women; it is a reductionist management strategy that partially perceives the forest. The public environmental management system, on the one hand, empowers public environmental institutions to manage and regulate forest resources considered technically fit for use; on the other hand, it promotes the conservation of biodiversity through natural protected areas, and should therefore address gender mainstreaming in all programs. Data collection in the field research conducted in 2014 was done through: eight semi-structured interviews with key actors, two group interviews differentiated by sex, four differentiated participatory workshops, and a survey of 33 women and 28 men. It was found that public institutions accentuate gender gaps through public programs aimed at women with no gender perspective, due to the lack of knowledge of the subject; so that, traditional division of labor is reinforced based solely on difference by sex.